(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Hepatitis B is a major public health problem worldwide, more than 350 million people have chronic infection in which may develop cirrhosis or cancer of the liver. The present study carried out among 61 previously diagnosed chronic hepatitis B patients. Among the 61 cases, 13(21.3%) were HBeAg positive and 48(78.7%) were HBeAg negative. In HBeAg positive cases, 53.85% had elevated and 46.15% had normal ALT levels. In contrast, majority (75%) of HBeAg negative patients had normal ALT levels. There was significance difference between HBeAg and ALT (p<0.05). In conclusion, the present study observed that there was positive correlation among HBeAg and ALT status in chronic HBV carriers. The combination of routine serology and biochemical test may be considered as an alternative to HBV DNA in evaluating the state of chronic HBV infection. JCMCTA 2016 ; 27 (2) : 60 - 62